2010
DOI: 10.3141/2189-03
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In-Vehicle and Infrastructure-Based Collision Warnings to Nonviolating Drivers at Signalized Intersections

Abstract: The potential effectiveness of warnings to drivers in imminent danger of collision with a red light violator was evaluated in an experiment that used a driving simulator. Three warnings were tested: (a) an infrastructure-based warning that immediately turned the traffic signal red and activated red wig-wag lights; (b) an in-vehicle warning that consisted of a brake pulse, voice annunciation, and activation of a red dashboard light; and (c) simultaneous activation of both warnings. Three warnings were tested wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In this study, the authors reported a mean of 0.4859 seconds and a standard deviation of 0.1538 seconds for drivers' responses to an amber signal, and a mean of 0.70 and a standard deviation of 0.316 for responses to an unexpected warning (either infrastructure-based or in-vehicle), suggesting a lower limit ! = 0.313 (12).…”
Section: Final Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the authors reported a mean of 0.4859 seconds and a standard deviation of 0.1538 seconds for drivers' responses to an amber signal, and a mean of 0.70 and a standard deviation of 0.316 for responses to an unexpected warning (either infrastructure-based or in-vehicle), suggesting a lower limit ! = 0.313 (12).…”
Section: Final Resultsmentioning
confidence: 99%
“…The Uniform distribution has an undesirable kink point in the CDF when awareness hits 100%, however, and it is because of this characteristic that the Uniform model seems relatively unrealistic compared to the alternatives. Literature suggests that the time it takes drivers to become aware of and respond to a change in their driving environment follows a Log-Normal distribution, with a standard deviation, σ a , equal to approximately half of the mean, µ a (10,11,12). However, it may not be appropriate to attempt to generalize these results to our current situation involving repeat exposure to environmental elements that may go unnoticed for several visits, so researchers may want to test other statistical distributions as well (e.g., Geometric, Uniform, Normal) and select the one that yields a driver response curve that best fits their improvement data for the "after" period.…”
Section: The Shape Of This Curve Is Determined By the Shapes Of The Dmentioning
confidence: 99%
See 1 more Smart Citation
“…It may not be possible to redirect the attention of these 16 drivers by a warning issued in the infrastructure. For example, a recent study by Inman and Davis (2009) investigated the potential effectiveness of in-vehicle and infrastructure based warnings to prevent red-light violations by vehicle drivers. The study showed that the infrastructure based warnings are less effective than the in-vehicle warnings.…”
Section: Hmi Positioning Requirementsmentioning
confidence: 99%
“…Previous research on red light violation warnings (RLVW) in simulated driving suggests potential benefits to presenting information through both the DVI and DII. Inman and Davis ( 13 ) concluded that simultaneous visual DII and a visual, auditory, and tactile DVI presentation of an intersection collision warning message was more effective than individual presentation through either individual method of communication: 95% of drivers were delayed 1 s (a delay time that would allow the red light violator to clear the intersection prior to the arrival of the participant, assuming constant speed) before their arrival at an intersection with a red light violator. The infrastructure-only and in-vehicle-only warnings delayed 67% and 80% of drivers, respectively.…”
mentioning
confidence: 99%